2017
DOI: 10.1097/md.0000000000008287
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of sonography in diagnosing volvulus in neonates with suspected intestinal malrotation

Abstract: This study is to prospectively evaluate the efficiency of sonography for volvulus diagnosis in neonates with clinically suspected intestinal malrotation.A total of 83 patients with suspected intestinal malrotation who underwent detailed abdominal sonography and upper gastrointestinal contrast study were included. Malrotation was characterized by inversion of the superior mesenteric artery (SMA) and superior mesenteric vein (SMV) in sonographic examination. The “whirlpool sign” of Color Doppler Sonography was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 22 publications
(39 reference statements)
1
33
3
3
Order By: Relevance
“…A previous study reported that the incidence of intestinal necrosis in cases with rotations of 720° or greater was 33.3%, whereas the incidence in cases with rotations of less than 720° was 6.7% . In our study, 1 of 4 cases (25%) with rotations of 720° or greater needed bowel resection, and 4 of 27 cases (15%) with rotations of less than 720° did not need bowel resection.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…A previous study reported that the incidence of intestinal necrosis in cases with rotations of 720° or greater was 33.3%, whereas the incidence in cases with rotations of less than 720° was 6.7% . In our study, 1 of 4 cases (25%) with rotations of 720° or greater needed bowel resection, and 4 of 27 cases (15%) with rotations of less than 720° did not need bowel resection.…”
Section: Discussionsupporting
confidence: 94%
“…In these 4 cases, 2 cases needed bowel resection due to tumor lesions and not intestinal necrosis. Therefore, our result was consistent with the previous report …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations